2023
DOI: 10.1002/rmv.2415
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine‐1‐phosphate related signalling pathways manipulating virus replication

Abstract: Viruses can create a unique cellular environment that facilitates replication and transmission. Sphingosine kinases (SphKs) produce sphingosine‐1‐phosphate (S1P), a bioactive sphingolipid molecule that performs both physiological and pathological effects primarily by activating a subgroup of the endothelial differentiation gene family of G‐protein coupled cell surface receptors known as S1P receptors (S1PR1‐5). A growing body of evidence indicates that the SphK/S1P axis is crucial for regulating cellular activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 110 publications
0
4
0
Order By: Relevance
“…Our findings also revealed that SPHK1 and SGPP2, the main enzymes that generated and degraded S1P, were both highly expressed during acute liver injury. Similarly, numerous studies have demonstrated that S1P plays a role in the regeneration and inflammation associated with various liver injuries, such as hepatic ischemia‒reperfusion 43 , liver fibrosis 44 , and hepatitis 45 . For instance, in a study on carbon tetrachloride-induced acute liver injury, SPHK1 mRNA expression and activity increased at 72 h, and S1P facilitated hepatic wound healing through S1PR2 46 , which suggested that S1P plays a role in liver regeneration following acute injury.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings also revealed that SPHK1 and SGPP2, the main enzymes that generated and degraded S1P, were both highly expressed during acute liver injury. Similarly, numerous studies have demonstrated that S1P plays a role in the regeneration and inflammation associated with various liver injuries, such as hepatic ischemia‒reperfusion 43 , liver fibrosis 44 , and hepatitis 45 . For instance, in a study on carbon tetrachloride-induced acute liver injury, SPHK1 mRNA expression and activity increased at 72 h, and S1P facilitated hepatic wound healing through S1PR2 46 , which suggested that S1P plays a role in liver regeneration following acute injury.…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory infections are common triggers of AECOPD. The SphK/S1P axis has been reported to regulate the host immune system and to exert pro- or anti-viral effects in different types of viral infections by interfering with intracellular signaling pathways ( 56 , 57 ). For example, S1P can enhance endothelial barrier function and epithelial cell survival during respiratory syncytial virus infection by activating the Akt/ERK signaling pathway ( 58 , 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, intracellular S1P can serve as a second messenger and bind to intracellular targets. For example, S1P can bind with prohibitin-2 (PHB2) to affect mitochondrial respiration in the mitochondria [ 27 ] and combine with histone deacetylases to influence gene expression in the nucleus [ 28 ].…”
Section: Overview Of S1pmentioning
confidence: 99%